Hub and Spoke: Next level in regional networks for infection prevention - Daniele Pantano; Alexander W. Friedrich (Elsevier, 2024)
The threat of multidrug-resistant organisms (MDROs) and antimicrobial resistance (AMR) are real and increasing every day. They affect not only healthcare systems but also communities, causing economic and public health concerns. Governments must take action to tackle AMR and prevent the spread of MDROs and regional hubs have a critical role to play in achieving this outcome. Furthermore, bacteria have no borders, consequently, cooperation networks should be extended between countries as a crucial strategy for achieving the success of infection control. Euregions, which are a specific form of cooperation between local authorities of two or more bordering European countries, can help solve common problems and improve the lives of people living on both sides of the border. Regional collaboration strategies can enhance infection control and build resilience against antimicrobial resistance. This review identifies risk factors and the correct approaches to infection prevention and control, including education and awareness programs for healthcare professionals, appropriate prescribing practices, and infection prevention control measures. These measures can help reduce the incidence of antimicrobial resistance in the region and save lives. It is therefore essential to take concrete actions and foster the creation of more effective regional and cross-border centers to ensure the success of infection control policies and the management of healthcare-associated infections. This work sheds light on the issue of MDRO infections within healthcare settings, while also acknowledging the crucial role of the One Health concept in understanding the broader context of these infections. By recognizing the interdependence of human and animal health and the environment, we can take constructive steps toward mitigating the risks of these infections and promoting better health outcomes for all.